Solitude(s) au Canada - Cros, Laurence; Dodeman, André; Eloy-Carriat, Isabelle; Fouache, Cécile; Harger-Grinling, Virginia; Kocevar, Savannah; Martin, Pierre; McPherson, Annika; Melançon, Johanne; Rainville, Lorie-Anne; Willis, Elizabeth (Études canadiennes / Canadian Studies, 2020)
Ce numéro thématique de la revue est né d’une idée originale de nos rédactrices invitées, Cécile Fouache (Université de Rouen Normandie) et Lorie-Anne Rainville (Université de Caen Normandie). Après les célébrations du cent-cinquantième anniversaire de la Confédération en 2017, et en ces temps de quête nationale pour la réconciliation avec les Premières Nations, elles ont souhaité apporter de nouvelles perspectives et des lectures innovantes autour du concept de solitude au Canada, via le prisme de la littérature et des arts. This thematic issue of the journal was born from an original idea of our guest writers, Cécile Fouache (University of Rouen Normandie) and Lorie-Anne Rainville (University of Caen Normandie). Following the celebrations of the centre-ineteenth anniversary of the Confederation in 2017, and in these times of national quest for reconciliation with the First Nations, they wanted to bring new perspectives and innovative readings around the concept of loneliness in Canada, through the prism of literature and the arts.